Survey of Global Health Education and Training in Pathology Residency Programs in the United States. Issue 3 (22nd November 2019) - Glynn, Emily H; Guarner, Jeannette; Hall, Allison; Nelson, Ann M; Andiric, Linda R; Milner, Dan A; Eichbaum, Quentin
Abstract: Objectives: This study assessed the prevalence, general interest, and barriers to implementing global health curricula in pathology residency programs. Methods: We conducted a survey of 166 US pathology residency programs. Results: Thirty-two (195) of 166 programs responded. Of these, 13% have a formalized global health program (n = 4), and the majority indicated at least some general interest in global health among trainees (88%, n = 28) and faculty (94%, n = 30), albeit at a low to moderate level. Funding limitations, regulatory constraints, and insufficient knowledge of global health were frequently cited barriers to developing a global health program. Conclusions: Few US pathology departments incorporate global health education into postgraduate training. The importance of pathology in global health has been underappreciated, despite its critical role in the delivery of health care in resource-limited settings. One solution is for pathology departments to expand global health educational opportunities for trainees.